Eficacia de tecnologías de nutrición sobre el rendimiento del maíz blanco para consumo en fresco, Calceta-Manabí - Basurto Marcillo, Edgar Vinicio (2021)
The objective of the research was to evaluate the efficacy of nutrition technologies on the yield and health of white corn for fresh consumption. The experiment was developed during the rainy season of 2020 in the Figueroa locality of the Bolívar canton, Manabí. The treatments evaluated were T1: NPK fertilization, T2: NPK fertilization + bioregulator cocktail, T3: NPK fertilization + soil improver + bioregulator cocktail, T4: Complete fertilization + soil improver + bioregulator cocktail, and T5: Control treatment. The main variables recorded were commercial ear production and net economic benefit (USD ha-1). The results obtained highlight that treatments T2, T3 and T4 reached the highest production of commercial ears, with increases of 31, 36 and 36% in relation to the control treatment, and 13, 19 and 18% in relation to the conventional treatment based on NPK. The highest net economic benefit was achieved with the T2 treatment, with 434 USD ha-1. The application of the bioregulator cocktail as a complement to the soil NPK fertilization, is decisive to increase the yield and profitability of the cultivation of white corn for fresh consumption.